The Relationship between Psychosocial Risk Factors and Burnout among Primary Healthcare Workers in Saudi Arabia - Waleed Homoud S Alonazi; Muteb Mohammed M Khubrani; Ali Al Shaikhi; Khafur Sayah K Al Ruwaili; Nasser Abdulwahab N Jamaan; Ebrahim Essa Essa Aqeel; Badr Nazal G Al Anazi; Mohammed Abdulrahman M Aloufi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim: This study explored the relationship between burnout and psychosocial risk factors in primary healthcare workers in Saudi Arabia’s public hospitals. Methods: Across-sectional studywas conducted through October and November 2024using a validated self-reportedonline questionnaire, including the Maslach Burnout Inventory and Copenhagen Psychosocial Questionnaire. Results: Participants showed lowoverall burnout levels. Some of the psychosocial risk factors showed a significant correlation with the burnout scale, whereas workers aged 28 years or below had more work-related insecurities than older workers(P=0.038). Conclusion: The findings showed that Saudi healthcare workers are less prone to burnout and psychosocial risk factors.